Design and performance analyses of graphene-nano plasmonic devices for wireless gas sensor applications. (29th March 2023) - Yakoub, Shaimaa E.; Kashyout, Abd El-Hady B.; Shoueir, Kamel; El-Kemary, Maged
Abstract: Graphene gained more attention in industrial applications owing to its unique characteristics. A simple and inexpensive photodeposition technique was used to fabricate the nanoparticles. Herein, ZnO, Au/ZnO, and the neat rGOx@Au/ZnO heterostructure plasmonic nanocomposites were applied to detect the sensitivity of CO2, LPG, and O2 gases using a sensing device with a rapid response at ambient temperature. The gas detection mechanism explains the synergistic influence between the localized plasmonic phenomena of AuNPs and the π-π interaction among rGOx/ZnO. Compared to pure ZnO and AuNPs/ZnO nanocomposite, the sensing response of rGOx@Au/ZnO (x = 10 wt %) exposed to CO2 gas is optimized, achieving a response of 625.63% over a 16-s reaction time at room temperature. The heterostructure's morphological, crystal structure, and electronic properties were determined using different techniques. The devices were exposed to various gases such as CO2, O2, and liquified petroleum gas (LPG) to test the selectivity of the composite sensor, and the sensor response for these gases was measured and significant. A wireless gas detector can be built using an Arduino module. The circuit is created by connecting a gas sensor to an Arduino rGOx@Au/ZnO (x = 10 wt %) weight board, which determines the gas content in the air and whether it exceeds the allowable value. At the level programmed in the Arduino kit, Global System Mobile (GSM) sends an SMS to the cell phone number that was also investigated. Highlights: AuNPs was deposited on the surface of ZnONPs via the photodeposition technique. rGO was added by π-π interaction to enhance the properties of the nanocomposite. Sensing response achieved against CO2, O2, and LPG gases. rGOx@Au/ZnO (x = 10 wt %) exhibited 625.63% over 16 s toward CO2 gas. A wireless gas detector was built using an Arduino module.